Implementation Of Water-Saving Technologies In Ferghana Valley And Its Results (1991-2018) (Texas Journal of Engineering and Technology, 2024)
The article analyzes, using scientific sources, important measures and events being taken to modernize the irrigation system in the Ferghana Valley regions, promising tasks in the introduction of water-saving technologies under the framework of fundamental reforms aimed at applying and studying modern methods and experiences in the irrigation system